2006
DOI: 10.5334/pb-46-1-2-117
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Implicit Self-Schemas and a Difficulty to Disengage from Negative Cognitions in Depression: An experimental psychopathology approach

Abstract: An experimental analysis of the processes characterising psychopathology and its maintenance have become an established research area, called experimental psychopathology. Vulnerability for depression can be conceptualised as a combination of the existence of latent depressogenic self-schemas and incapacity to disengage from depressogenic cognitions. Therefore, the most recent research of our lab focused on these separate aspects of information processing. Based on measures of implicit cognition, remarkable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In line with Borkovec's (1994) suggestion that worry can be seen as a cognitive avoidance strategy, and given the overlap between worry and rumination, avoidance might be the mechanism underlying rumination in depression (De Raedt, 2006). Detailed representations or memories (e.g., traumatic past events) can be avoided by deliberately ruminating about one's depressed state in abstract terms (e.g., How should I go on with my life?).…”
Section: Author Notementioning
confidence: 66%
“…In line with Borkovec's (1994) suggestion that worry can be seen as a cognitive avoidance strategy, and given the overlap between worry and rumination, avoidance might be the mechanism underlying rumination in depression (De Raedt, 2006). Detailed representations or memories (e.g., traumatic past events) can be avoided by deliberately ruminating about one's depressed state in abstract terms (e.g., How should I go on with my life?).…”
Section: Author Notementioning
confidence: 66%
“…Hospitalized SAs were more sensitive in gazing toward suicide images in the SA group, which is a line with studies about the relationship between suicidality and the source of patients (Pfeffer et al, 1986; Table S3-E and Figure S3-B1, B2 in the online supplemental materials). Group differences were not significant for disengagement latency for suicide images, which was not expected based on previous depression and anxiety research (De Raedt, 2013;Ellenbogen & Schwartzman, 2009;Sanchez et al, 2013). One reason is that we were using the average latency of the whole trial instead of the latency of initially disengaging away from suicide-AOI, to reflect the ability of elaborative attention control.…”
Section: Sustained Attentionmentioning
confidence: 70%
“…Implicit association, often referred as implicit attitude, has been formed for a long time since childhood based on own experiences [31]. De Raedt [32] indicated that the implicit association had similarity to depressive schema in the context of cognitive behavior theory for depression. These characteristics of implicit association would make maintaining of experimental change to be difficult.…”
Section: Discussionmentioning
confidence: 99%